Protection for Saviour Sibling Children Reviewed from, Medical Bioethics and Indonesian Positive Law - Susanti, Yulia; Syofyan, Syofirman; Mannas, Yussy Adelina (Dinasti Research, 2025)
The development of assisted reproductive technologies such as In Vitro Fertilization (IVF) and Preimplantation Genetic Diagnosis (PGD) currently allows the birth of a child for the purpose of saving a sick sibling through a stem cell transplant or better known as saviour sibling. This practice was first successfully carried out in 2000 and continues to grow to this day around the world. This article aims to examine the bioethical aspects and legal arrangements related to the practice of saviour sibling in Indonesia, which until now has no specific regulations despite the continuous development of related technologies. The research method used is normative legal research, with qualitative analysis of primary, secondary, and tertiary legal materials. This article compares the arrangements of saviour sibling practices in several countries to identify the principles relevant to the regulation in Indonesia. The results of the study showed that this practice has significant benefits, such as saving the lives of patients with hematopoietic disorders, but also poses physical and psychological risks to children born as saviour sibling. This article recommends the need for special arrangements in Indonesia that cover aspects of ethics, law, and child welfare to ensure their implementation responsibly